Gender differences in the health status of elderly living alone, compared to those who are not alone: Evidence of the AHAP study, North of Iran - Simin Mouodi; Ali Bijani; Seyed Reza Hosseini; Karimollah Hajian-Tilaki (Babol University of Medical Sciences, 2016)
Background: One of the factors that have impact on the health status of elderly people is living alone. This study was conducted to examine the living condition of elderly population in Babol and probable differences which this condition induced on the health disorders of elderly people. Methods: This cross-sectional study was performed on 1544 elderly people aged 60 and over in Amirkola, Babol. Demographic characteristics, the incidence of falls, chronic diseases, polypharmacy, headache with uncertain cause, chronic pains and back pain were collected by the study questionnaire; social support, physical activity, depression and cognitive disorders were assessed with standard questionnaires. Results: 6.8% of elderly people were living alone. Lack of social support, cognitive disorders, depression, multiple chronic diseases, occurrence of falls and headache with uncertain cause were significantly higher among those elderly who live alone (p<0.05). Regardless of age and educational level, headache and depressive symptoms in male individuals living alone, and falls occurrence in female individuals were significantly more than those who did not live alone (p<0.05 ). Also, in female elderly subjects, the effect of the marital status factor on health-related disorders was more than the effect of living alone factor. Conclusion: Many disorders and disabilities are higher in the elderly people who live alone; also there is a difference in the health status of elderly people who live alone, according to their gender.